Rg3-enriched ginseng extract ameliorates scopolamine-induced learning deficits in mice. Issue 1 (December 2016) - Kim, Jiyoung; Shim, Jaesung; Lee, Siyoung; Cho, Woo-Hyun; Hong, Eunyoung; Lee, Jin; Han, Jung-Soo; Lee, Hyong; Lee, Ki
Abstract Background Ginseng (Panax ginseng C.A. Meyer) has been used as a traditional herb in the treatment of many medical disorders. Ginsenosides, which are triterpene derivatives that contain sugar moieties, are the main pharmacological ingredients in ginseng. This study was designed to investigate the effect of ginsenoside Rg3-enriched ginseng extract (Rg3GE) on scopolamine-induced memory impairment in mice. Methods Rg3GE (50 and 100 mg/kg) were administered to C57BL/6 mice by oral gavage for 14 days (days 1–14). Memory impairment was induced by scopolamine (1 mg/kg, intraperitoneal injection) for 6 days (days 914). The Morris water maze test was used to assess hippocampus-dependent spatial memory. The effects of scopolamine with or without Rg3GE on acetylcholinesterase and nuclear factor-κB (NF-κB) in the hippocampus were also examined. Results Mice with scopolamine treatment alone showed impairments in the acquisition and retention of spatial memory. Mice that received Rg3GE and scopolamine showed no scopolamine-induced impairment in the acquisition of spatial memory. Oral administration of Rg3GE suppressed the scopolamine-mediated increase in acetylcholinesterase activity and stimulation of the NF-κB pathway (i.e., phosphorylation of p65) in the hippocampus. Conclusion These findings suggest that Rg3GE may stabilize scopolamine-induced memory deficits through the inhibition of acetylcholinesterase activity and NF-κB signaling in the hippocampus.